The petrogenesis of the volcanic rocks of the Witwatersrand triad in the Klerksdorp area, Transvaal - Bowen, Michael Peter (Rhodes University, Faculty of Science, Department of Geology, 1985)
Several hundred chemical analyses of early Proterozoic lavas of the Witwatersrand triad (incorporating the Dominion Group, Witwatersrand Supergroup and Ventersdorp Supergroup) in the Klerksdorp area, have revealed the presence of various distinct magma types. These essentially correspond to formally defined lithostratigraphic units, but several inconsistencies have necessitated the use of informal nomenclature. The lavas have been regionally metamorphosed to low-grade, greenschist facies assemblages. Original igneous textures are preserved, despite a metamorphic overprint. Metamorphism has resulted in a certain degree of random chemical remobilization. Ba, Sr, Rb, K₂0, Na₂0 and CaO have been highly mobile, and their usefulness in petrogenetic modelling is extremely limited. In contrast, Zr, Nb, Y, LREE's, Cr, Ni, Ti0₂ P₂0₅ and Al₂0₃ have remained immobile. Ti/Zr and Ti/P ratios together constitute efficient discriminating variables for characterizing the different magma types. Lava compositions range from primitive Mg-rich tholeiites to rhyolites, the bulk being tholeiitic andesites. Al₂0₃ contents do not exceed 15%, a feature which reflects the tholeiitic, as opposed to calcalkaline, character of these lavas. Two magma-types are present within the Dominion Group, which is a typical example of bimodal volcanism. The Dominion basic lavas are overlain by the Dominion acid porphyries, with a limited amount of interfingering. The basic lava suite is highly fractionated, with compositions ranging from Mg-, Cr- and Ni-rich tholeiites (close to primary mantle melts) to evolved tholeiitic andesites. The most primitive liquids evolved by 45% fractional crystallization of hornblende, followed by a further 70% crystallization of an orthopyroxene-plagioclase assemblage containing up to 3% sulphides. The Dominion porphyries are rhyolitic, display very limited compositional variation, and probably represent a crustal melt related to the same magmatic event which produced the basic lavas. The only lavas from the Witwatersrand Supergroup present in the Klerksdorp area are those of the Crown Formation (Jeppestown amygdaloid). These are tholeiitic dacites which display extremely limited compositional variation, and are unrelated to any of the other magmas of the Witwatersrand triad. The Ventersdorp Supergroup comprises 4 magma-types: The Kliprivierberg Group lavas at the base are subdivisible into 3 sub-types on the basis of Zr contents. (Zr>11Oppm) are the most evolved. They are tholeiitic andesites which display fairly limited compositional variation. It is likely that more evolved compositions are present in other areas where the porphyritic lavas which characterize this unit are better developed. The overlying Orkney lavas are characterized by 110ppm>Zr>90ppm. They are tholeiitic andesites of similar composition to the Alberton lavas, but have lower incompatible element levels, higher siderophile element levels, and are of extremely uniform composition. The uppermost Loraine/Edenville lavas range from magnesian tholeiites to tholeiitic andesites. They are distinguished by Zr< 90ppm, and contain the most primitive magmas af the Witwatersrand triad, with up to 17,5% MgO, 2600ppm Cr, 600ppm Ni and M-values up to 77. The most primitive liquids evolved by 38% fractional crystallization of orthopyroxene ∓ chromite, followed by 35% fractional crystallization of an extract containing clinopyroxene and plagioclase. The absence of olivine precipitation is a result of the inherently high Si0₂ content of the magma. The Loraine/Edenville, Orkney and Alberton lavas do not lie on a common liquid line of descent, but are probably consanguinous. The Platberg Group overlies the Kliprivierberg Group, and has a coarse-clastic sedimentary unit, the Kameeldoorns Formation, at the base. Three petrographically distinct porphyritic lava sequences overlie the Kameeldoorns Formation, namely the informal "Goedgenoeg formation", the Makwassie quartz-feldspar porphyries and the Rietgat Formation. Despite petrographic differences, the Goedgenoeg and Rietgat lavas are chemically indistinguishable and thus form a single magma-type. The Makwassie porphyries are dacitic in composition with a high proportion of feldspar and quartz phenocrysts. Rational variation trends are attributed to a nett loss of Si0₂ during secondary alteration. The porphyries are probably of crustal origin. The Goedgenoeg/Rietgat lavas display unusual chemistry and a broad, irrational compositional spectrum. They contain very high incompatible element levels, high nonnative quartz, as well as high MgO, M-values, Cr and Ni relative to the other tholeiitic andesites of the Witwatersrand triad. It is tentatively suggested that they are hybrid magmas containing both crust and mantle components, the former possibly represented by the Makwassie porphyries. Field evidence suggests that Platberg volcanism commenced directly after Klipriviersberg volcanism ceased, and was accompanied by a period of enhanced tectonic activity. The Platberg lavas thus probably reflect a crustal melting cycle associated with the Klipriviersberg magmatic event. The Allanridge lavas are the youngest rocks of the Witwatersrand triad. They are separated from the Platberg Group by a unit of flat-lying sediments, the Bothaville Formation, which was deposited after an extended period of peneplanation. The Allanridge lavas form a separate magma-type. They are tholeiitic andesites of similar composition to the Alberton lavas, but have higher incompatible element levels and are not consanguinous. The compositional similarities amongst the basic magma-types of the Witwatersrand triad suggests that all were generated in an hydrous mantle. Interelement ratio differences between the various magma-types nevertheless support the concept that the mantle was chemically heterogeneous during the early Proterozoic.
Keywords: Volcanic rocks; Witwatersrand triad; Klerksdorp; Transvaal; Northwest Province; South Africa; Chemical analysis; Magma; Geology